2009
DOI: 10.1074/jbc.m806618200
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Effects of Charged Residues in the Intracellular Loop on Ion Permeation in α1 Glycine Receptor Channels

Abstract: The Cys loop receptor channels mediate fast synaptic transmission in the nervous system. The M2-demarcated transmembrane pore is an important determinant of their ion permeation properties. Portals within the intracellular domain are also part of the permeation pathway in cationic Cys loop receptors, with charged residues in a helical MA stretch partially lining these openings profoundly affecting channel conductance. It is unknown whether analogous portals contribute to the permeation pathway in anionic Cys l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
59
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 26 publications
(25 reference statements)
3
59
0
Order By: Relevance
“…The mutation of charged residues near M4 has been shown to alter single channel conductance in homomeric 5-HT 3 R and GlyRs; in both cases the mutations were made within a putative homolog of the MA stretch (29,32). In our study ␣1(K378E) induced a significant decrease in single channel chord conductance ( Figs.…”
Section: Discussionsupporting
confidence: 47%
See 2 more Smart Citations
“…The mutation of charged residues near M4 has been shown to alter single channel conductance in homomeric 5-HT 3 R and GlyRs; in both cases the mutations were made within a putative homolog of the MA stretch (29,32). In our study ␣1(K378E) induced a significant decrease in single channel chord conductance ( Figs.…”
Section: Discussionsupporting
confidence: 47%
“…At present, the theory of ion permeation in pLGICs relies on the concept that canonical rings of charged residues make integral electrostatic interactions with permeant ions to control permeation and selectivity (10,12). Recent functional data in 5-HT 3 R, nAChR, and GlyR demonstrated that the ILD also plays a role in this process (29,31,32,35). Therefore, we hypothesized that deletion of the ␣1 ILD of the GABA A R would change the effective geometry of the permeation pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding GlyRs, it was shown that replacement of all basic amino acids present in the IL to negatively charged residues produced a strong impact on the GlyR, rendering it nonfunctional. In addition, simultaneous mutations of arginine and lysine at positions 377, 378, 385, and 386 to glutamate reduced the conductance of the channel, showing their importance in channel function (Carland et al, 2009). Furthermore, the correct assembly of GlyR seems to depend on the presence of the RFRRKRR cluster in the intracellular loop (Sadtler et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…For example, it was reported that the IL regulates nAChR and GlyR channel gating via G␤␥ binding (Fischer et al, 2005;Yevenes et al, 2006). In addition, a single residue (Arg436) in the IL of the human 5-HT 3A receptor was found to regulate channel conductance (Deeb et al, 2007;Carland et al, 2009). Furthermore, another study showed that the most important residue controlling the actions of G␤␥ and ethanol on GlyRs was Lys385 (Yevenes et al, 2008).…”
Section: Introductionmentioning
confidence: 99%